Th1-related transcription factors and cytokines in systemic lupus erythematosus - Tang, Yang-Yang; Wang, Da-Cheng; Chen, You-Yue; Xu, Wang-Dong; Huang, An-Fang (Frontiers in Immunology, 2023)
Systemic lupus erythematosus (SLE) is an inflammatory disorder related to immunity dysfunction. Th1 cell family including Th1 cells, transcription factor T-bet and related cytokines IFNγ, TNFα, IL-2, IL-18, TGF-β, IL-12, who have been widely discussed in autoimmunity, such as SLE. In this review, we will comprehensively discuss expression profile of Th1 cell family both in SLE patients and animal models, and clarify how the family members involve in lupus development. Interestingly, T-bet related age-associated B cells (ABCs) and low dose IL-2 treatment in lupus were emergently discussed as well. Collection of the evidence will better understand roles of Th1 cell family in lupus pathogenesis, especially targeting IL-2 in lupus.